THE EFFECTS OF SIMPLE PAST TENSE AND VOCABULARY MASTERY TOWARDS STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Nurliani Nurliani; Venny Eka Meidasari (INFERENCE: Journal of English Language Teaching, 2019)
Abstract: This research is a kind of survey and aims to determine the effects of simple past tense and vocabulary mastery towards students' writing skills in recount text at SMPN Lebak Regency. The 67 samples were gained through the cluster, proportional, and random sampling. The gained data were then analyzed by using the multiple regressions method. These research results are: 1) There are any significant effects of simple past tense and vocabulary mastery jointly towards students' writing skills in recount text. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 24.561; 2) There is a significant effect of simple past tense mastery towards students' writing skills in recount text. It is proved by Sig.= 0.000 < 0.05 and tobserved = 3.764; 3) There is a significant effect of vocabulary mastery towards students' writing skills in recount text. It is proved by Sig.= 0.000 < 0.05 and tobserved = 4.974.  Keywords: Simple past tense; Vocabulary mastery; Writing skills; EFL